A 16.6 μW 3.12 MHz RC relaxation oscillator with 160.3 dBc/Hz FOM - Zhou, Wei (2020)
This paper presents a new RC relaxation oscillator for biomedical sensor interface circuit. A novel switch-capacitor based RC charging/discharging circuit is proposed to effectively improve the oscillator phase noise and power performance. The inverter-based comparator with replica biasing is employed and optimized to enhance the phase noise performance and to lower output dependence on the supply voltage variation. The oscillator's temperature insensitivity is also improved by resistor temperature compensation. The prototype RC relaxation oscillator circuit is designed in a commercial 65nm CMOS process. The post-layout simulation results showed 3.12 MHz output frequency, -112dBc/Hz phase noise at 100 kHz offset, and 16.6 μW power consumption under 1 V supply voltage. The frequency variation is ±0.294%/V for supply within 1 V to 1.6 V, and 11.31 ppm/°C for temperature across -40°C to 100°C. The overall circuit performance is compared favorably to the state-of-art designs, with an outstanding Figure of Merit (FOM) of 160.03 dBc/Hz at 100 kHz.